Revisiting decade-old questions in proanthocyanidin biosynthesis: current understanding and new challenges - Lu, Nan (Frontiers in Plant Science, 2024)
Proanthocyanidins (PAs), one of the most abundant natural polymers found in plants, are gaining increasing attention because of their beneficial effects for agriculture and human health. The study of PA biosynthesis has been active for decades, and progress has been drastically accelerated since the discovery of key enzymes such as Anthocyanidin Reductase (ANR), Leucoanthocyanidin Reductase (LAR), and key transcription factors such as Transparent Testa 2 (TT2) and Transparent Testa 8 (TT8) in the early 2000s. Scientists raised some compelling questions regarding PA biosynthesis about two decades ago in the hope that addressing these questions would lead to an enhanced understanding of PA biosynthesis in plants. These questions focus on the nature of starter and extension units for PA biosynthesis, the stereochemistry of PA monomers and intermediates, and how and where the polymerization or condensation steps work subcellularly. Here, I revisit these long-standing questions and provide an update on progress made toward answering them. Because of advanced technologies in genomics, bioinformatics and metabolomics, we now have a much-improved understanding of functionalities of key enzymes and identities of key intermediates in the PA biosynthesis and polymerization pathway. Still, several questions, particularly the ones related to intracellular PA transportation and deposition, as well as enzyme subcellular localization, largely remain to be explored. Our increasing understanding of PA biosynthesis in various plant species has led to a new set of compelling open questions, suggesting future research directions to gain a more comprehensive understanding of PA biosynthesis.